Comparison of the Clinical Value of miRNAs and Conventional Biomarkers in AMI: A Systematic Review - Wang, Baofu; Li, Yang; Hao, Xuezeng; Yang, Jingjing; Han, Xiaowan; Li, Haiyan; Li, Tong; Wang, Dayang; Teng, Yu; Ma, Liang; Li, Yao; Zhao, Mingjing; et al. (Frontiers in Genetics, 2021)
Background/Aims: To compare the clinical value of the peak time point and area under the curve (AUC) of miRNAs and conventional biomarkers in acute myocardial infarction (AMI). Methods: A literature search was carried out in PubMed, Web of Science, Embase and Cochrane systematically. Screening studies, extracting data and assessing article quality were performed independently by two researchers. Also, the names of miRNAs in the included studies were standardized by the miRBase database. Results: A total of 40 studies, encompassing 6960 participants, were included in this systematic review. Circulating miRNAs, especially in the plasma, were the main research sample. The results of this systematic review display that miR-1-3p, miR-19b-3p, miR-22-5p, miR-122-5p, miR-124-3p, miR-133a/b, miR-134-5p, miR-150-5p, miR-186-5p, miR-208a, miR-223-3p, miR-483-5p and miR-499a-5p reached peak time earlier and showed a shorter time window than the conventional biomarkers despite the different collection times of initial blood samples. MiR-1-3p, miR-19b-3p, miR-133a/b, miR-208a/b, miR-223-3p, miR-483-5p and miR-499a-5p show more valuable than classical biomarkers for the early diagnosis of AMI, and these miRNAs appeared to within 4h of the onset of symptoms except miR-133a/b and miR-208b. Moreover, combined miRNAs or combined miRNAs with classical biomarkers could compensate for the deficiency of single miRNAs and conventional biomarkers in sensitivity or specificity for an optimal clinal value. Conclusions: MiR-1-3p, miR-19b-3p, miR-208a, miR-223-3p, miR-483-5p and miR-499a-5p are promising biomarkers for AMI due to the satisfactory diagnostic accuracy and short time window (within 4h of the onset of symptoms).